Depression Increases Stroke Hospitalization Cost: An Analysis of 17, 010 Stroke Patients in 2008 by Race and Gender. (10th March 2013) - Husaini, Baqar; Levine, Robert; Sharp, Linda; Cain, Van; Novotny, Meggan; Hull, Pamela; Orum, Gail; Samad, Zahid; Sampson, Uchechukwu; Moonis, Majaz
Abstract : Objective . This analysis focuses on the effect of depression on the cost of hospitalization of stroke patients. Methods . Data on 17, 010 stroke patients (primary diagnosis) were extracted from 2008 Tennessee Hospital Discharge Data System. Three groups of patients were compared: (1) stroke only (S O, n = 7, 850 ), (2) stroke + depression (S + D, n = 3, 965 ), and (3) stroke + other mental health diagnoses (S + M, n = 5, 195 ). Results . Of all adult patients, 4.3% were diagnosed with stroke. Stroke was more prevalent among blacks than whites (4.5% versus 4.2%, P < 0.001 ) and among males than females (5.1% versus 3.7%, P < 0.001 ). Nearly one-quarter of stroke patients (23.3%) were diagnosed with depression/anxiety. Hospital stroke cost was higher among depressed stroke patients (S + D ) compared to stroke only (S O ) patients ($77, 864 versus $47, 790, P < 0.001 ), and amongS + D, cost was higher for black males compared to white depressed males ($97, 196 versus $88, 115, P < 0.001 ). Similar racial trends in cost emerged amongS + D females. Conclusion . Depression in stroke patients is associated with increased hospitalization costs. Higher stroke cost among blacks may reflect the impact of comorbidities and the delay in care of serious health conditions. Attention to early detection of depression in stroke patients might reduce inpatient healthcare costs.